ANALISIS KEBUTUHAN PENGEMBANGAN SDM UNTUK MENINGKATKAN KINERJA PEGAWAI DALAM DI BKP KELAS I MATARAM - Agussaleh Agussaleh; Agusdin Agusdin; Hermanto Hermanto (Distribusi - Journal of Management and Business, 2020)
The purpose of this study is to analyze the HR Development Needs to Improve Employee Performance in the Implementation of ISO 9001: 2015 QMS in BKP Class I Mataram. This research is a qualitative research, the informant criteria used in this study is someone who has the authority to regulate, supervise, audit and implement directly related to the continuation of the implementation of ISO 9001: 2015 QMS in BKP Mataram. Qualitative data analysis consists of three activities that are carried out simultaneously, namely data reduction, data presentation and drawing conclusions. The results showed that BKP Class I Mataram had developed HR and implemented the ISO 9001: 2015 QMS to improve employee and organizational performance, efforts to improve theperformance were carried out starting: 1). organizational development (OD) in the form of implementing work systems through the implementation of Quality Management Standards through ISO 9001: 2015, SNI ISO 17025 for laboratory of accreditation and ISO 37001 on anti-bribery management systems; 2) Non-Apparatus Development through the quarantine socialization; 3) Apparatus of Development through increasing the level of education to a higher level; 4) Apparatus through quarantine basic training and Training Center; 5) Apparatus of Training in the form of training activities, in-house training, workshops and mental development of employees.